Global Infectious Diseases between September and December 2023: Periodical Analysis - Junzi Liao; Yufan Wu; Yinfu Sun; Qi Xiang; Taihan Li; Yi Luo; Guodan Li; Wenjin Yu; Dongliang Liu; Shiping He; Dayong Gu (Zoonoses, 2024)
A plethora of infectious diseases have plagued mankind since the dawn of civilization. Historically, humans have suffered from a range of infectious diseases, including MPOX, Ebola virus, dengue virus, malaria, and influenza. Many respiratory infectious diseases are more likely to occur in cold weather. Due to the speed and easy mode of transmission, and short latency, respiratory infectious diseases are more likely to cause epidemics. It is more likely that influenza will circulate during the autumn-winter months, resulting in great outbreaks of influenza-like illnesses and even serious seasonal epidemics in some cases. We obtained surveillance data from the Shusi Tech’s Global Epidemic Information Monitoring System and comprehensively analyzed the timing and location of outbreaks in infected populations from September-December 2023.